An avian influenza H7 DNA priming vaccine is safe and immunogenic in a randomized phase I clinical trial - DeZure, Adam D.; Coates, Emily E.; Hu, Zonghui; Yamshchikov, Galina V.; Zephir, Kathryn L.; Enama, Mary E.; Plummer, Sarah H.; Gordon, Ingelise J.; Kaltovich, Florence; Andrews, Sarah; McDermott, Adrian; Crank, Michelle C.; et al. (npj vaccines, 2017)
A novel avian influenza subtype, A/H7N9, emerged in 2013 and represents a public health threat with pandemic potential. We have previously shown that DNA vaccine priming increases the magnitude and quality of antibody responses to H5N1 monovalent inactivated boost. We now report the safety and immunogenicity of a H7 DNA-H7N9 monovalent inactivated vaccine prime-boost regimen. In this Phase 1, open label, randomized clinical trial, we evaluated three H7N9 vaccination regimens in healthy adults, with a prime-boost interval of 16 weeks. Group 1 received H7 DNA vaccine prime and H7N9 monovalent inactivated vaccine boost. Group 2 received H7 DNA and H7N9 monovalent inactivated vaccine as a prime and H7N9 monovalent inactivated vaccine as a boost. Group 3 received H7N9 monovalent inactivated vaccine in a homologous prime-boost regimen. Overall, 30 individuals between 20 to 60 years old enrolled and 28 completed both vaccinations. All injections were well tolerated with no serious adverse events. 2 weeks post-boost, 50% of Group 1 and 33% of Group 2 achieved a HAI titer ≥1:40 compared with 11% of Group 3. Also, at least a fourfold increase in neutralizing antibody responses was seen in 90% of Group 1, 100% of Group 2, and 78% of Group 3 subjects. Peak neutralizing antibody geometric mean titers were significantly greater for Group 1 (GMT = 440.61, p < 0.05) and Group 2 (GMT = 331, p = 0.02) when compared with Group 3 (GMT = 86.11). A novel H7 DNA vaccine was safe, well-tolerated, and immunogenic when boosted with H7N9 monovalent inactivated vaccine, while priming for higher HAI and neutralizing antibody titers than H7N9 monovalent inactivated vaccine alone. Avian influenza: A vaccine for a deadly emergent strain A vaccine candidate to treat a deadly subtype of avian influenza was shown to induce protective antibodies in initial clinical trials. As of March 2017, avian influenza strain A/H7N9 has killed 497 people since 2013, with 1349 confirmed cases. Julie Ledgerwood and her team from the United States’ National Institutes of Health in collaboration with colleagues at the Centers for Disease Control and Prevention tested their two-stage vaccine protocol in humans, showing it to be effective and safe. The vaccine consists of an initial injection of viral DNA, which ‘primes’ the immune system to the pathogen, followed by a follow-up injection of an inactivated purified viral protein, which further boosts the host’s production of protective antibodies. The study shows the viability of this vaccine regimen and suggests further investigation into its appropriateness for treating avian influenza in humans.